عدن : نشاطها التجاري والحياة الاجتماعية لتجارها في الفترة 5-7هـ/11-13م - فسيل، سامية محمد عبد الله (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
The objective of the study is to examine the most important commercial of the city of Aden in Yemen from the fifth to the seventh centuries after the Hijra/the eleventh to the thirteen centuries CE, and to discuss the Factors that gave Aden an important status in international trade. The study also examines the impact of commercial activities on the demographic structure of the Aden community, and discusses the emergence of social classes that had a leading role in commercial and social life of the city. In discussing these topics, the researcher depended on an analytical and descriptive approach, and consulted a large number of primary and secondary sources dealing with the topic. Finally, the study came of conclusion that the geographical location of Aden had a significant influence in designing its commercial role that had its impact on the political and social structure of Aden.